Carbon dioxide emission from brickfields around Bangladesh - Imran, MA; Baten, MA; Nahar, BS; Morshed, N (International Journal of Agricultural Research, Innovation and Technology, 2015)
The study was undertaken at six divisions of Bangladesh to investigate the CO2 emission from brickfields. to explore the rate of carbon emission over the last 10 years, based on existing technology for brick production. The finding reveals that there were more than 45,000 Brick kilns in Bangladesh which together account for about 95% of operating kilns including Bull's Trench Kiln, Fixed Chimney Kiln, Zigzag Kiln and Hoffman Kiln. These kilns were the most carbon emitting source but it varies on fuel type, kiln type and also for location. It has been found that, maximum carbon emission area was Chittagong, which was 93.150 with percentage of last 10 years and 9.310 per cent per year. Whereas Sylhet was lower carbon emission area indicating percentage 17.172 of last 10 years and 4.218 percent per year. It has been found that total annual amount of CO2 emission for 4 types brick kilns from Dhaka, Chittagong, Rajshahi, Khulana, Sylhet and Barisal were 8.862 Mt yr-1, 10.048 Mt yr-1, 12.783 Mt yr-1, 15.250 Mt yr-1, in the year of 2002, 2005, 2007 and 2010 respectively. In Mymensingh district, the maximum CO2 emission and coal consumption was obtained in Chamak brick field, which was 1882 tons and 950 tons, respectively and minimum was obtained in Zhalak brick field, which was 1039.5 tons and 525.0 tons, respectively during the year of 2013. The percentage in last 10 years of CO2 emission was 72.784 and per cent per year 7.970, which is very alarming for us. The estimates obtained from surveys and on-site investigations indicate that these kilns consume an average of 240 tons of coal to produce 1 million bricks. This type of coal has a measured calorific value of 6,400 KJ, heating value of coal is 20.93 GJ t-1 and it produces 94.61 TJ t-1 and 56.1 TJ t-1 CO2 from coal and natural gas, respectively. DOI: http://dx.doi.org/10.3329/ijarit.v4i2.22653 Int. J. Agril. Res. Innov. & Tech. 4 (2): 70-75, December, 2014